Temperature‐Mediated Microfluidic Extrusion of Structurally Anisotropic Hydrogels. Issue 6 (13th February 2019) - Khuu, Nancy; Alizadehgiashi, Moien; Gevorkian, Albert; Galati, Elizabeth; Yan, Ning; Kumacheva, Eugenia
Abstract: In this study, microfluidic extrusion of structurally anisotropic hydrogel sheets formed by cellulose nanocrystal methacrylate (CNC‐MA) and gelatin methacryloyl (Gel‐MA) is reported. The precursor CNC‐MA/Gel‐MA ink has temperature‐responsive and shear‐thinning properties, which make it compatible with extrusion‐based printing. To preserve shear‐induced CNC‐MA alignment, the extruded hydrogels are cooled down and photocrosslinked. It is shown that by varying the cooling temperature, the degree of structural anisotropy of the CNC‐MA/Gel‐MA hydrogels can be controlled, which is further augmented by varying the volumetric flow rate during extrusion. The structural anisotropy of the hydrogels is preserved at physiological temperatures (37 °C) for 7 days. The hydrogel sheets exhibit anisotropic mechanical and swelling properties with enhanced mechanical strength and reduced swelling along the extrusion direction. The design and use of this hydrogel expands the ability to create structurally anisotropic hydrogels with applications in biological and biomedical research, soft robotics and fundamental studies of anisotropy‐induced properties. Abstract : Fabrication of structurally anisotropic hydrogels has wide applications in tissue engineering and fundamental investigation of anisotropy‐mediated properties . Here, a composite hydrogel composed of cellulose nanocrystal methacrylate and gelatin methacryloyl for the extrusion of structurally anisotropic hydrogel sheets, where temperature is used to control the extent of alignment, is shown.